Narrating life : experiments with human and animal bodies in literature, science and art - Herbrechter, Stefan (Experimental practices (Brill Rodopi (Firm)) ;, 2016)
Narrating Life explores the relationship between literature, science and the arts and the way in which they are informed by the process of narrating life. More specifically, it asks: how do literature, science and the arts affect and are affected by the emergence of a critical culture of biopolitics and its rhetorical figurations? Its topicality for literary and cultural studies lies therefore in its exploration of the question: to what extent could narratives of life (or life-writing) be understood as a special practice through which to access the contemporary discussion about biopolitics with its strategies of immunity, mutation, and contagion. The individual contributions address these questions through focusing on new forms of life writing in traditional and new media, science writing and artistic and critical creative practice. In doing so, they also explore and redraw the boundaries between fictional and factual experimental practices. Contributors: Amelie Björck, Elisabeth Friis, Holly Henry, Stefan Herbrechter, Tom Idema, Moritz Ingwersen, Cristina Iuli, Tanja Nusser, Angela Rawlings, Manuela Rossini, Dorion Sagan, Laura Shackelford, Amalie Smith, Marianne Sommer, Steve Tomasula, David Wagner , Jeff Wallace, Dominik Zechner.